2008
DOI: 10.1248/bpb.31.273
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Macelignan on Cisplatin-Induced Hepatotoxicity Is Associated with JNK Activation

Abstract: In the clinical field, the most important form of toxic hepatic injury is caused by therapeutic agents. Drug-induced liver injury is the most frequent reason for the withdrawal of an approved drug from the market, and it is also responsible for more than 50% of cases of acute liver failure in the United States.1) More than 600 drugs have been associated with hepatotoxicity, and there are now a number of reports that reactive metabolites formed from drugs such as acetaminophen, tamoxifen, diclofenac, and trogli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Previous studies have reported the role of reactive oxygen species (ROS) in mediating the kidney and liver toxicity of xenobiotics [32,33]. CDDP increases the intracellular production of oxygen and nitrogen species in the kidney and liver by increasing the activity of cytochrome P450 enzymes, NADPH oxidase, xanthine oxidase, and adenosine deaminase [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the role of reactive oxygen species (ROS) in mediating the kidney and liver toxicity of xenobiotics [32,33]. CDDP increases the intracellular production of oxygen and nitrogen species in the kidney and liver by increasing the activity of cytochrome P450 enzymes, NADPH oxidase, xanthine oxidase, and adenosine deaminase [34].…”
Section: Discussionmentioning
confidence: 99%
“…32,33) It is well known that PPARg agonists elicit anti-inflammatory and anti-amyloidogenic effects and that MAPK has emerged as a key factor in the regulation of Tau and b-amyloid precursor proteins. 10,34) This study explored possible anti-inflammatory mechanisms related to MAPKs by macelignan in LPS-stimulated BV-2 microglias cells.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the hepatoprotective activity of myristicin may be, at least in part, due to the inhibition of TNF-alpha release from macrophages. Sohn et al (2008) observed that the hepatoprotective effects of macelignan, isolated from M. fragrans is related to activation of the mitogen activated protein kinase (MAPK) signaling pathway, especially JNK and c-Jun.…”
Section: Aphrodisiac Activitymentioning
confidence: 99%